Analisis Kondisi Kerusakan dan Prioritas Penanganan Jalan Menggunakan PKRMS dengan Pendekatan Surface Distress Index dan Road Condition Index (Studi Kasus: Ruas Jalan Malimbu-Pengempus Sari, Kabupaten Lombok Utara) - Rio Handika; Anwar Efendy; Muhammad Khalis Ilmi (Jurnal Talenta Sipil, 2026)
Roads are a vital land transportation infrastructure that supports community mobility and regional economic development. However, as the service life of a pavement increases, its condition gradually deteriorates due to repeated traffic loading and environmental factors. If not properly managed, pavement deterioration may reduce the level of road service, increase the risk of traffic accidents, and raise vehicle operating costs. Therefore, periodic pavement condition evaluation is essential to identify the extent of deterioration and to determine appropriate maintenance priorities. This study aims to assess pavement conditions using the Provincial/Kabupaten Road Management System (PKRMS) through the Surface Distress Index (SDI) method, evaluate the functional condition of the road using the Road Condition Index (RCI) method, and determine maintenance priorities for the Malimbu–Pengempus Sari Road in North Lombok Regency. A visual pavement survey was conducted on 51 road segments, and the collected data were processed using the PKRMS application to obtain SDI and RCI values as well as maintenance recommendations. The SDI analysis indicated that 17 segments (33.33%) required routine maintenance, 21 segments (41.18%) required periodic maintenance, and 13 segments (25.49%) required reconstruction. The highest SDI value of 265 was identified at STA 1+600–1+700, STA 2+300–2+400, STA 2+500–3+400, STA 4+000–4+200, and STA 4+400–4+600, where the predominant pavement distresses consisted of potholes and surface deformation. Meanwhile, the RCI values ranged from 4.00 to 6.00, indicating that the functional condition of the road varied from fair to good. The integration of SDI and RCI through the PKRMS application produced maintenance priorities dominated by periodic maintenance, followed by routine maintenance and reconstruction, according to the condition of each road segment. The findings demonstrate that integrating SDI and RCI within the PKRMS framework provides a more objective and comprehensive basis for determining road maintenance priorities by considering both the structural and functional conditions of the pavement.